Emerging CO2 capture systems. (September 2015) - Abanades, J.C.; Arias, B.; Lyngfelt, A.; Mattisson, T.; Wiley, D.E.; Li, H.; Ho, M.T.; Mangano, E.; Brandani, S.
Highlights: Some emerging CO2 capture processes have increased their TRL from 2–3 to 6 since the publication of the IPCC SRCCS (2005). Chemical looping, calcium looping, solid sorbents and membranes can rely on mature technologies in other industries. Their cost structure confirms that they may become major technology competitors if there is ever a market for CCS. New findings in the fields of functional materials, reactor improvements and process design may lead to new developments. Abstract: In 2005, the IPCC SRCCS recognized the large potential for developing and scaling up a wide range of emerging CO2 capture technologies that promised to deliver lower energy penalties and cost. These included new energy conversion technologies such as chemical looping and novel capture systems based on the use of solid sorbents or membrane-based separation systems. In the last 10 years, a substantial body of scientific and technical literature on these topics has been produced from a large number of R&D projects worldwide, trying to demonstrate these concepts at increasing pilot scales, test and model the performance of key components at bench scale, investigate and develop improved functional materials, optimize the full process schemes with a view to a wide range of industrial applications, and to carry out more rigorous cost studies etc. This paper presents a general and critical review of the state of the art of these emerging CO2 capture technologies paying special attention to specific process routes that have undergone a substantial increase in technical readiness level toward the large scales required by any CO2 capture system.